2017
DOI: 10.1186/s12879-017-2890-y
|View full text |Cite
|
Sign up to set email alerts
|

The global effect of maternal education on complete childhood vaccination: a systematic review and meta-analysis

Abstract: BackgroundThere is an established correlation between maternal education and reduction in childhood mortality. One proposed link is that an increase in maternal education will lead to an increase in health care access and vaccine uptake. Vaccinations are a central preventative child health tool, therefore demonstrating the importance of understanding factors that can improve coverage. This review aims to establish if there is a correlation between increasing maternal education and vaccine uptake and if this va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 42 publications
7
73
0
1
Order By: Relevance
“…Similarly, mothers with higher educational status might be aware of the preventive role of immunization service compared to women with no education. A metanalysis on the role of maternal education on childhood vaccination also showed that maternal education plays a more important role in lower-income countries than in high-income countries (33).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, mothers with higher educational status might be aware of the preventive role of immunization service compared to women with no education. A metanalysis on the role of maternal education on childhood vaccination also showed that maternal education plays a more important role in lower-income countries than in high-income countries (33).…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in rural Nigeria found that mother's knowledge of immunization was significantly correlated with full immunization [16]. Other studies also found that maternal education was a determinant of immunization [8,11,14,15,[17][18][19][20]. However, several other studies didn't find evidence of association between maternal education and immunization [14,17,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, higher maternal education level was demonstrated a determinant of the timely childhood vaccination. We assumed that a high education level would help mothers get a better understanding and acceptance of vaccination knowledge in practice, through a better communication with vaccination providers [ 17 , 18 ]. Fifth, mothers with fixed jobs might not have enough time to spend on the childhood immunization or have time constraints due to the inflexible working hours.…”
Section: Discussionmentioning
confidence: 99%